2017
DOI: 10.1088/1361-6463/aa5068
|View full text |Cite
|
Sign up to set email alerts
|

Transition from single to multiple axial potential structure in expanding helicon plasma

Abstract: Transition from single to multiple axial potential structure (MAPS) formation is reported in expanding helicon plasma. This transition is created by forming a cusp magnetic field at the downstream after the expansion throat. Two distinct potential drops are separated by a uniform axial potential zone. Non-uniform axial density distribution exists in expanding helicon systems. A cusp-like field nourishes both the axial density gradients sufficient enough for the formation of these two distinct potential drops. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…It is also observed that this high-density plasma source could be a viable option for electric propulsion systems, and has received great attention in the helicon double layer thruster community [10][11][12]. Its current-free nature in lowcollisional, magnetically expanding, inductive-or wave-mode discharges distinguishes helicon double layers [12][13][14] from other current-driven double layers. The DL in the plateau region of mirror magnetic field topology was also investigated [5,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also observed that this high-density plasma source could be a viable option for electric propulsion systems, and has received great attention in the helicon double layer thruster community [10][11][12]. Its current-free nature in lowcollisional, magnetically expanding, inductive-or wave-mode discharges distinguishes helicon double layers [12][13][14] from other current-driven double layers. The DL in the plateau region of mirror magnetic field topology was also investigated [5,15].…”
Section: Introductionmentioning
confidence: 99%
“…In a brief communication, an emissive probe wire was proposed by Lafleur et al [25] to take measurements of the potential in an expanding helicon plasma. Recently Ghosh et al [14] also used the emissive probe to measure multiple DLs. Sahu et al [15] used a new RF-compensated Langmuir probe structure to acquire the plasma potential from the maximum of the first order differential of the current-voltage curve.…”
Section: Introductionmentioning
confidence: 99%
“…1 The ion beam appears in low pressure, expanding helicon plasmas regardless of source size, magnetic field ratio (upstream to downstream), and overall magnetic field strength. [2][3][4][5] The spontaneous creation of ion beams in an expanding plasma is of particular relevance to the development of helicon source plasma thrusters, 6,7 to solar wind acceleration models, 8 and to particle acceleration processes during magnetic reconnection. 9 Soon after their discovery, various researchers proposed explanations for the ion beam creation process that focused on current-free, double layers (DLs) as the phenomenon responsible for the ion beams.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh et al created the transition from single to multiple axial potential structure by forming a cusp magnetic field in the downstream of the diffusion chamber. They pointed out that only when geometric and magnetic expansions closely coincide with each other could single and multiple DL‐like structures appear [24]. Charles [25] found a two‐dimensional (2D) high‐density conic along the most diverging magnetic field lines exiting the source in helicon plasma device, which was also reported by Saha et al [26] that radial density profile in the downstream was peaked on the periphery appearing a hollow profile.…”
Section: Introductionmentioning
confidence: 88%